ANTESEDEN KINERJA KARYAWAN PT BANK MALUKU DAN MALUKU UTARA CABANG AMBON - Kowey, Wylda Olivia (Jurnal Minds: Manajemen Ide dan Inspirasi, 2018)
This study aims to analyze the factors that become determinants of employee performance of PT Bank Maluku and North Maluku Ambon Branch. Data were collected using questionnaires distributed to 103 employees of PT Bank Maluku and North Maluku Ambon Branch. The data collected was further processed and calculated using SPSS 21 and then analyzed using descriptive analysis and path analysis. The results show that compensation has a positive and significant influence both directly and indirectly on job satisfaction and employee performance. In addition, work motivation also has a positive and significant influence either directly or indirectly on job satisfaction and employee performance. Similarly, the work environment has a positive and significant impact on job satisfaction and employee performance either directly or indirectly. And job satisfaction has a positive and significant impact on employee performance. Furthermore, the results of this study recommend that in order to form job satisfaction and performance of employees, it is suggested that the management of PT Bank Maluku North Maluku should always pay attention to the compensation, both financial and non-financial, motivation of work, both intrinsic as well as extrinsic, and the creation of a good and conducive internal working environment.